A minimum facility method for in vitro collection of Digitaria eriantha sspentzii and Cynodon dactylon - Ruredzo, T.J. (1991)
Simple in vitro techniques were developed for collecting Digitaria eriantha sspentzii and Cynodon dactylon to obviate deterioration, quarantine and bulk problems of conventional methods for collecting vegetative material. Various antimicrobial agents were tested for effective surface-sterilization of plant material and for microbial contamination. Halazon tablets were used for surface-sterilization and a combination of Rifamycine and Benlate was the most effective medium supplement. Includes data on the effect of different combinations of antimicrobial agents on the performance of in vitro cultures of D. eriantha and performance of in vitro cultures and resulting potted plants as well as growth parameters of in vitro cultures and of potted plants.